1992
DOI: 10.1002/em.2850190204
|View full text |Cite
|
Sign up to set email alerts
|

Induction of prophage lambda by chlorinated organics: Detection of some single‐species/single‐site carcinogens

Abstract: Twenty-eight chlorinated organic compounds were evaluated for their ability to induce DNA damage using the Microscreen prophage-induction assay in Escherichia coli. Comparison of the performance characteristics of the prophage-induction and Salmonella assays to rodent carcinogenicity assays showed that the prophage-induction assay had a somewhat higher specificity than did the Salmonella assay (70% vs. 50%); sensitivity, concordance, and positive and negative predictivity were similar for the two microbial ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Notable pharmacologic agents which induce prophages include mitomycin C, used in chemotherapy, and numerous antibiotics, including the fluoroquinolones, often used in treatment of diarrhea (41). Interestingly, endogenous products of inflammatory cells, such as H 2 O 2 , are also known to induce lambdoid prophages (12). While it remains unknown to what extent such exogenous and endogenous factors contribute to STEC pathogenesis, our study suggests that clinical intervention to prevent prophage induction may reduce Stx production during STEC infection.…”
Section: Discussionmentioning
confidence: 76%
“…Notable pharmacologic agents which induce prophages include mitomycin C, used in chemotherapy, and numerous antibiotics, including the fluoroquinolones, often used in treatment of diarrhea (41). Interestingly, endogenous products of inflammatory cells, such as H 2 O 2 , are also known to induce lambdoid prophages (12). While it remains unknown to what extent such exogenous and endogenous factors contribute to STEC pathogenesis, our study suggests that clinical intervention to prevent prophage induction may reduce Stx production during STEC infection.…”
Section: Discussionmentioning
confidence: 76%
“…MX binds strongly to protein [Haataja et al 19911, and the potential binding of MX to DNA gyrase could account for the extraordinary potency of MX in the prophage-induction assay. We have also shown that this assay can detect as genotoxic those chlorinated organics that produce free radicals that may cause DNA strand breaks [Houk andDeMarini, 1987, 1988;DeMarini et al, 1990;DeMarini and Brooks, 1992;DeMarini and Lawrence, 19921. MX has been reported to have the potential to produce free radicals [Tuppurainen and Lotjonen, 1993;LaLonde and Leo, 1994;LaLonde et al, 19941 as well as DNA adducts [Meier et al, 1989;Sheet et al, 19911.…”
Section: Genotoxicity Of MX In E Coli and Salmonellamentioning
confidence: 87%
“…1,1,2,2-Tetrachloroethane is considered by the U.S. Fnvironmental Ptoection Agency (EPA) to be a possible human carcinogen on the basis of tumor indtiction in male and female mice, although it was negative in male and female rats for carcinogenicity (184) ( Table 5). It is mutagenic and shows other evidence of genotoxicity: it is positive for inducing DNA repair (187), SCE (162), and DNA damage (prophage lambda test in Escherichia coli) (188), and is positive in the replicative DNA synthesis test (166). No data relevant to reproductive toxicity were located.…”
Section: Ch2-ch2-ci Smentioning
confidence: 99%